Changes in the long-term hydrological regimes and the impacts of human activities in the main Wei River, China. Issue 6 (25th April 2016) - Zhang, Hongbo; Huang, Qiang; Zhang, Qiang; Gu, Lei; Chen, Keyu; Yu, Qijun
ABSTRACT: Under the combined influence of climate changes and human activities, the hydrological regime of the Wei River shows remarkable variations which have caused many issues in the Wei River in recent decades, such as a lack of freshwater, water pollution, disastrous flooding and channel sedimentation. Hence, hydrological regime changes and potential human-induced impacts have been drawing increasing attention from local government and hydrologists. This study investigates hydrological regime changes in the natural and measured runoff series at four hydrological stations on the main Wei River and quantifies features of their long-term change by analysing their historical annual and seasonal runoff data using several approaches, i.e., continuous wavelet transform, cross-wavelet, wavelet coherence, trend-free pre-whitening Mann-Kendall test and detrended fluctuation analysis. By contrasting two different analysis results between natural and measured river runoff series, the impacts of human activities on the long-term hydrological regime were investigated via the changes of spatio-temporal distribution in dominant periods, the trends and long-range memory of river runoff. The results show : (a) that periodic properties of the streamflow changes are the result of climate, referring to precipitation changes in particular, while human activities play a minor role; (b) a significant decreasing trend can be observed in the natural streamflow series along the entire main stream of the Wei River and the more serious decrease emerging in measured flow should result from human-induced influences in recent decades; and (c) continuous decreasing streamflow in the Wei River will trigger serious shortages of freshwater in the future, which may challenge the sustainability and safety of water resources development in the river basin, and should be paid great attention before 2020.Editor Z.W. Kundzewicz;Associate editor K. Hamed